2014
DOI: 10.2139/ssrn.2435112
|View full text |Cite
|
Sign up to set email alerts
|

R&D Policy and Schumpeterian Growth: Theory and Evidence

Abstract: In recent years, a large body of empirical research has investigated whether the predictions of secondgeneration growth models are consistent with actual data. This strand of literature has focused on the longrun properties of these models by using productivity and innovation data but has not directly assessed the effectiveness of R&D policy in promoting innovation and economic growth. In the present paper, we fill this gap in the literature by providing a unified growth setting that is empirically tested with… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 91 publications
(112 reference statements)
1
3
0
Order By: Relevance
“…Multi-band photometry for a huge number (∼23000) of southern field RRLs has also been released by CATALINA (Drake et al 2013;Torrealba et al 2014). Similar findings have been provided in the NIR bands by VVV for RRLs in the Galactic bulge (Minniti et al 2014) and by VMC (Moretti et al 2015, in preparation) for RRL in the MCs. New optical catalogs have also been released by large optical surveys such as SDSS and Pan-STARRS1 (Abbas et al 2014) and UV surveys such as GALEX (Gezari et al 2013;Kinman & Brown 2014).…”
Section: Introductionsupporting
confidence: 77%
“…Multi-band photometry for a huge number (∼23000) of southern field RRLs has also been released by CATALINA (Drake et al 2013;Torrealba et al 2014). Similar findings have been provided in the NIR bands by VVV for RRLs in the Galactic bulge (Minniti et al 2014) and by VMC (Moretti et al 2015, in preparation) for RRL in the MCs. New optical catalogs have also been released by large optical surveys such as SDSS and Pan-STARRS1 (Abbas et al 2014) and UV surveys such as GALEX (Gezari et al 2013;Kinman & Brown 2014).…”
Section: Introductionsupporting
confidence: 77%
“…The seminal studies in this literature are Romer (1990), Segerstrom et al (1990), Grossman and Helpman (1991) and Aghion and Howitt (1992). Subsequent studies in this literature apply variants of the R&D-based growth model to explore the e¤ects of patent protection and R&D subsidies on innovation and economic growth; 3 see for example Peretto (1998) Minniti and Venturini (2014) and Kiedaisch (2015). These studies focus on a representative-household framework and do not consider the distributional implications of patent protection and R&D subsidies.…”
Section: Introductionmentioning
confidence: 99%
“…Conclusions indicating a long-run effect of tax incentives on R&D activities were drawn by Minniti and Venturini (2013) based on an analysis of nineteen industries in the U.S. between 1975 and 2000. Their study indicated that subsidies on research activity increase the R&D efforts and economic growth rates, but only temporarily.…”
Section: Literature Reviewmentioning
confidence: 99%